Kinerja Perusahaan Batik Trusmi Cirebon Dalam Kaitannya Dengan Inovasi Produk dan Pemasaran - Afifah, Nurul; Pringgabayu, Dematria; Arfiansyah, Ferry (Income Journal: Accounting, Management and Economic Research, 2023)
Batik is a work of art and cultural heritage recognized by UNESCO. Indonesian people are attached to batik, both in formal and non-formal events. This study aims to determine the effect of product innovation and promotion through social media on the performance of batik companies in the Trusmi Cirebon batik center. The analysis was conducted using Path Analysis with the help of SPSS software. Data was collected from 80 respondents who are batik entrepreneurs in Cirebon. The results showed that the product innovation variable had a positive and significant effect on company performance. Social media promotion variables have a positive and significant influence on company performance. Both variables together also have a positive and significant effect on company performance . Companies need to manage their social media professionally so that the content presented is interesting and in turn will improve company performance